DEVELOPMENT OF ECOTOURISM IN SPECIALLY PROTECTED NATURAL AREAS OF THE KAMCHATKA TERRITORY: ANALYSIS OF INFRASTRUCTURAL APPROACHES AND ARCHITECTURAL SOLUTIONS - Kasimova, Adema (International Journal of Professional Business Review, 2024)
Objective: To study and identify effective methods and approaches for creating ecotourism infrastructure in the Kamchatka Territory, ensuring the balance between tourism development and the preservation of natural complexes.Methods: The research employs an analysis of regulatory documents, design guidelines, and existing ecotourism facilities. It examines urban planning techniques, architectural solutions, and construction technologies relevant to ecotourism in specially protected natural areas (SPNAs).Results: The study reveals limitations in the existing infrastructure, such as insufficient visitor centers, ecological trails, and sanitary facilities. Recommendations include the integration of functional and environmentally sustainable designs, improved accessibility, and enhanced visitor experiences through modern architectural and infrastructural solutions.Conclusions: The proposed infrastructural and architectural approaches provide a foundation for the sustainable development of ecotourism in Kamchatka. These methods aim to enhance tourism potential while minimizing environmental impact, ensuring a harmonious coexistence between natural preservation and economic growth.